Fine particulate pollution concentration in Addis Ababa exceeds the WHO guideline value: Results of 3 years of continuous monitoring and health impact assessment. Issue 3 (7th June 2021) - Kumie, Abera; Worku, Alemayehu; Tazu, Zelalem; Tefera, Worku; Asfaw, Araya; Boja, Getu; Mekashu, Molla; Siraw, Dawit; Teferra, Solomon; Zacharias, Kristin; Patz, Jonathan; Samet, Jonathan; et al.
Abstract : Background: Real-time monitoring of fine particulate matter (PM2.5 ) concentrations and assessing the health impact are limited in Ethiopia. The objective of this study is to describe current levels of PM2.5 air pollution in Addis Ababa and examine temporal patterns and to consider the health impact of current PM2.5 exposure levels. Methods: PM2.5 concentrations were measured using a centrally-located Beta Attenuator Monitor (BAM-1022) for 3 years (1 April 2017 to 31 March 2020), with data downloaded biweekly. Deaths attributable to current PM2.5 concentration levels were estimated using the AirQ+ tool. The daily average was estimated using hourly data. Results: The daily mean (SD) PM2.5 concentration was 42.4 µg/m 3 (15.98). Two daily extremes were observed: morning (high) and afternoon (low). Sundays had the lowest PM2.5 concentration, while Mondays to Thursdays saw a continuous increase; Fridays showed the highest concentration. Seasons showed marked variation, with the highest values during the wet season. Concentration spikes reflected periods of intensive fuel combustion. A total of 502 deaths (4.44%) were attributable to current air pollution levels referenced to the 35 µg/m 3 WHO interim target annual level and 2, 043 (17.7%) at the WHO 10 µg/m 3 annual guideline. Conclusion: PM2.5 daily levels were 1.7 times higher than the WHO-recommended 24-hour guideline. The current annual mean PM2.5 concentration results in a substantial burden of attributable deaths compared to an annual mean of 10 µg/m 3 . The high PM2.5 level and its variability across days and seasons calls for citywide interventions to promote clean air.